Assessment of Microbiology Students’ Progress With an Audience Response System - M. Ahmad Chaudhry (American Society for Microbiology, 2011)
The development of new approaches to teaching of large lecture courses is needed. Today’s classroom has a wide range of students including high-achieving motivated learners, students struggling to understand basic concepts, and learning-challenged students. Many of these students can be lost in large classes under the shadow of the high-achieving extroverted students who dominate classroom question-and-answer sessions. Measuring a student’s understanding and achievement of content standards becomes difficult until an assessment has been done. To close this gap, an audience response system was introduced in an introductory Principles of Microbiology course. This technology specifically addressed the goal of individualizing instruction to the needs of the students. The evaluation of this project indicated an overall positive impact on student learning.